Insufficiency fractures in patients treated with pelvic radiotherapy and chemotherapy for uterine and cervical cancer. (25th July 2013) - Mehmood, Q.; Beardwood, M.; Swindell, R.; Greenhalgh, S.; Wareham, T.; Barraclough, L.; Livsey, J.; Davidson, S.E.
<x xml:space="preserve">Abstract</x> Insufficiency fractures are recognised consequences of radiotherapy in gynaecological malignancy with reported incidences between 2.7% and 89%. We aimed to determine the incidence and risk factors for insufficiency fractures in patients receiving radical pelvic radiotherapy for uterine and cervical cancer. A case‐note review was undertaken of patients treated between January 2007 and December 2008. Insufficiency fractures were identified from radiographs, computed tomography and magnetic resonance images. Chi‐squared and Mann–Whitney tests were performed to determine associations between insufficiency fractures and chemotherapy, steroids and age. A total of 285 patients received pelvic radiotherapy, 137 with uterine and 148 with cervical cancer. Mean age was 59 years. A total of 144 patients received chemotherapy, 101 concurrently and 35 adjuvantly. Bone abnormalities affected 67 patients, 33 had pelvic insufficiency fractures, 12 had multiple fractures and 3 patients developed femoral head avascular necrosis. Use of chemotherapy was not associated with development of fractures (P = 0.949). However, cervical cancer patients had a significantly higher incidence of insufficiency fractures (P = 0.018) and bone pain (P = 0.03) compared with uterine cancer patients. This suggests concurrent chemotherapy may be a significant factor in increasing insufficiency fractures and bone morbidity in these patients and highlights a need for further research to identify, prevent and reduce these long‐term complications.